2005
DOI: 10.5483/bmbrep.2005.38.1.049
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression and Genomic Organization of Genes Encoding Major Royal Jelly Protein 1 and 2 of the Honey Bee (Apis cerana)

Abstract: Major Royal Jelly Protein cDNAs of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…In addition to A. mellifera, the genomes of three related honey bee species-Apis cerana, Apis dorsata, and Apis florea-have genes encoding MRJPs (Albertova et al 2005;Imjongjirak et al 2005;Su et al 2005). These data support the following two conclusions: The mrjp duplication events were recent, and the distribution of mrjp genes within animals is very restricted.…”
Section: Drapeau Et Alsupporting
confidence: 60%
“…In addition to A. mellifera, the genomes of three related honey bee species-Apis cerana, Apis dorsata, and Apis florea-have genes encoding MRJPs (Albertova et al 2005;Imjongjirak et al 2005;Su et al 2005). These data support the following two conclusions: The mrjp duplication events were recent, and the distribution of mrjp genes within animals is very restricted.…”
Section: Drapeau Et Alsupporting
confidence: 60%
“…In addition to these obvious advantages in using insect cell lines for solving the CCD issue, we and others have demonstrated that production of insect venom allergens in insect cells is generally superior in terms of functionality, epitope authenticity and folding . That this also holds true for MRJPs is underlined by the only other report concerning the recombinant production of MRJPs, MRJP1 and MRJP2 from Apis cerana , which could be produced in Escherichia coli only in insoluble form .…”
Section: Discussionmentioning
confidence: 95%
“…The Yellow gene family from which MRJPs are derived (pfam03022) is widespread within the Arthropoda, but MRJPs are currently unknown beyond the genus Apis . It is noteworthy that A. mellifera , A. cerana , A. dorsata and A. florea are all highly eusocial (Michener, 1974), and all have genes encoding MRJPs (Albertova et al ., 2005;Imjongjirak et al ., 2005;Su et al ., 2005). Whether the phylogenetic association between sociality and MRJPs is significant has not yet been tested, but the apparent coevolution between the two characters suggests that certain MRJPs evolved to help signal or regulate the expression of social traits, possibly including worker sterility.…”
Section: Discussionmentioning
confidence: 99%